PENGEMBANGAN E-COMIC SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KECAKAPAN HIDUP ANAK USIA DINI - Aini Indriasih; Sumaji Sumaji; B. Badjuri; S. Santoso (Universitas Muria Kudus, 2020)
This study aims to develop e-comics as a learning medium to improve life skills of young children. The approach used is research and development. This research method is a mixed methods design. The subjects in this study were kindergarten students group B, teachers and head master Batik Kindergarten Kudus. Data collection techniques were carried out using questionnaires, observations, interviews, and documentation. e-comic was developed referring to the stages of development carried out by Borg and Gall. The results showed that e-comic learning media is feasible to be applied in learning to improve early life skills of children. Quantitatively, the assessment of material experts is (3.87) in either category. Expert assessments are based on curriculum appropriateness, correctness of content and ways of presenting the material included in both categories), and media expert assessments obtained scores (4.0) media expert assessments are based on production considerations, visual design, and technical quality, scores (4.0) in either category. While the assessment given by students in the field test stage (3.88), wider field test (3.99), and operational test (3.91), the acquisition of the score indicates that the e-comic learning media is categorized as good, which means that e-comic learning media are effectively used to improve early life skills. Qualitatively, e-comic media as a learning medium to improve life skills can attract students' attention to learning, facilitate student learning, and stimulate students to remember material more easily.